KOMPENSASI TENAGA PENDIDIK PRESPEKTIF TAFSIR IBN KATSIR DAN RELEVANSINYA DALAM MANAJEMEN PENDIDIKAN : Analisis Penafsiran QS Al-Baqarah [2] Ayat 41 - Sofi'i, Shokhib (Jurnal Manajemen Pendidikan Islam Al-Munadzomah, 2024)
Educators are entitled to a decent life, but some people tend to view that in the process of teaching educators must be sincere and do not allow compensation for them with the arguments of the Qur'an, one of which adheres to QS. Al-Baqarah [2]:41. The purpose of this research is: To find out how the legality and compensation system of educators in Tafsir Ibn Kathir and its relevance in Islamic education management. This research is a qualitative literature study with Tafsir Ibn Kathir as the primary data plus other interpretations, books and journals related to educators' compensation. The data is obtained through an in-depth study of the commentaries and then connected with the theories related to educators' compensation. The results of this study are: educators' compensation is legalized in Tafsir Ibn Katsir which is also supported by Islamic jurists. In Tafsir Ibn Katsir, it is explained about the compensation system of public and private educators, as well as the amount of educator compensation. What Ibn Katsir explains about educators' compensation is relevant to education management, but Ibn Katsir also explains the concept of sincerity in teaching.